Search for supersymmetry in pp collisions at √s=7TeV in final states with missing transverse momentum and b-jets with the ATLAS detector - Aad, G; Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abouzeid, O; Abramowicz, H; et al. (2012)
The results of a search for supersymmetry in events with large missing transverse momentum and heavy-flavor jets using an integrated luminosity corresponding to 2.05fb-1 of pp collisions at √s=7TeV recorded with the ATLAS detector at the Large Hadron Collider are reported. No significant excess is observed with respect to the prediction for standard model processes. Results are interpreted in a variety of R-parity conserving models in which scalar bottoms and tops are the only scalar quarks to appear in the gluino decay cascade, and in an SO(10) model framework. Gluino masses up to 600-900GeV are excluded, depending on the model considered. © 2012 CERN. Published by the American Physical Society.